Operational Conditions for an Internal Combustion Engine in a SOFC-ICE Hybrid Power Generation System - Victor A. Reyes-Flores; Zachary Swartwout; Shane Garland; Daniel B. Olsen; Bret Windom; Robert Braun; Todd Bandhauer (Energies)
Hybrid power generation systems utilizing pressurized Solid Oxide Fuel Cells (SOFCs) have gained considerable attention recently as an effective solution to the increasing demand for cleaner electricity sources. Among the various hybridization options, gas turbines (GT) and internal combustion engines (ICE) running on SOFC tail gas have been prominent. Although spark ignition (SI) tail gas engines have received less focus, they show significant potential for stationary power generation, particularly due to their ability to control combustion. This research experimentally characterized an SI engine fueled by simulated SOFC anode gas for five blends, which correspond to overall system power level and loads. The study aimed to optimize the engine operating conditions for each fuel blend and establish operational conditions that would sustain maximum performance. The results showed efficiencies as high as 31.4% at 1600 RPM, with a 17:1 compression ratio, equivalence ratio (φ) of 0.75, and a boost pressure of 165 kPa with low NOx emissions. The study also emphasizes the benefits of optimizing boost supply to minimize parasitic loads and improve brake thermal efficiency. Additionally, installing a catalytic oxidizer would enable the system to comply with new engine emission regulations. A proposed control scheme for automation includes regulating engine power by controlling the boost of the supercharger at a fixed throttle position. The results of this study help to promote the development of this SOFC-based clean energy technology.